Deuteronomy 21:1-9 a programmatic anomaly? : a thematic and programmatic analysis of Deuteronomy 21:1-9 within the context of the Deuteronomist’s agenda - Robinson, A. G. (Stellenbosch : Stellenbosch University, 2016)
Thesis (MTh)--Stellenbosch University, 2015.